The effect of content marketing on purchase intention through customer engagement as variable mediation - Maheza Prasetya; Daniel Susilo (Jurnal Komunikasi Profesional, 2022)
This study aims to determine whether or not the influence of content marketing from the @Planetban Instagram account on consumers purchase intentions through customer engagement. This study uses several concepts such as social media marketing, content marketing, purchase intention, and customer engagement. The results of this study showed that there is the influence of content marketing on purchase intention mediated by R-Square results explain the influence of content marketing (X) and customer engagement (Y1) is able to explain the variability of purchase intention (Y2) construct of 52.8% and the remaining 47.2% explained by other constructs outside the studied in this study. The results show that in influencing consumer purchase intention indirectly, Planet Ban successfully utilizes Instagram @Planetban as a container to conduct marketing activities wrapped in a message strategy through content marketing to create a purchase intention response in the minds of consumers through customer engagement.